2013
DOI: 10.1063/1.4800550
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional magnetic interactions and magnetism of high-density charges in a polymer transistor

Abstract: Magnetic interactions and magnetism of high-density charges in a polymer transistor were investigated by electron spin resonance (ESR). The anisotropy of the ESR spectra indicated an edge-on molecular orientation and the existence of two-dimensional magnetic interactions between the spins of the charges, reflecting high charge density. The voltage dependences revealed that the magnetism of charge carriers changed from paramagnetic to nonmagnetic as charge density increased. These results provide insight to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Electron spin resonance (ESR) is one promising method for such a microscopic characterization of charge-accumulation sites because it is a highly sensitive and powerful approach that is capable of investigating organic devices at the molecular level [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Electron spin resonance (ESR) is one promising method for such a microscopic characterization of charge-accumulation sites because it is a highly sensitive and powerful approach that is capable of investigating organic devices at the molecular level [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Electron spin resonance (ESR) spectroscopy is suitable for such microscopic characterization, because it can investigate organic semiconductors and their devices at the molecular level. Actually, we have clarified spin states of charge carriers and their spin concentration not only in organic semiconducting materials [24] but also in organic semiconductor devices such as organic field-effect transistors (OFETs) [25][26][27] and OPVCs [28,29]. Our ESR investigations are also involved in the charge-carrier states of radical cations in a typical hole-transporting material [30] and radical anions in a typical organic light-emitting material tris(8-hydroxyquinoline) aluminum (Alq 3 ) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Electron spin resonance (ESR) is a promising method for microscopic characterization because it is highly sensitive and can be utilized to investigate organic materials and devices at the molecular level. [17][18][19][20] ESR can be used to investigate the correlation between microscopic ESR parameters and the macroscopic deterioration of the performance of solar cells. 20 Li et al have reported that the LiF buffer layer is modified by the post-annealing.…”
mentioning
confidence: 99%